It is currently 20 Nov 2017, 08:43

### GMAT Club Daily Prep

#### Thank you for using the timer - this advanced tool can estimate your performance and suggest more practice questions. We have subscribed you to Daily Prep Questions via email.

Customized
for You

we will pick new questions that match your level based on your Timer History

Track

every week, we’ll send you an estimated GMAT score based on your performance

Practice
Pays

we will pick new questions that match your level based on your Timer History

# Events & Promotions

###### Events & Promotions in June
Open Detailed Calendar

# f(x)=5x^3-2x+8 and g(x)=6x-4 what is g((f(x))

Author Message
Intern
Joined: 22 Sep 2007
Posts: 32

Kudos [?]: 2 [0], given: 0

f(x)=5x^3-2x+8 and g(x)=6x-4 what is g((f(x)) [#permalink]

### Show Tags

20 Oct 2007, 11:45
This topic is locked. If you want to discuss this question please re-post it in the respective forum.

f(x)=5x^3-2x+8 and g(x)=6x-4

what is g((f(x))?

Kudos [?]: 2 [0], given: 0

VP
Joined: 10 Jun 2007
Posts: 1434

Kudos [?]: 370 [0], given: 0

### Show Tags

20 Oct 2007, 11:58
inwosu wrote:
f(x)=5x^3-2x+8 and g(x)=6x-4

what is g((f(x))?

g((f(x)) = g(5x^3-2x+8)
= 6*(5x^3-2x+8) - 4
= 30x^3 - 12x + 44

Kudos [?]: 370 [0], given: 0

Director
Joined: 11 Jun 2007
Posts: 909

Kudos [?]: 292 [0], given: 0

### Show Tags

20 Oct 2007, 11:59
bkk145 wrote:
inwosu wrote:
f(x)=5x^3-2x+8 and g(x)=6x-4

what is g((f(x))?

g((f(x)) = g(5x^3-2x+8)
= 6*(5x^3-2x+8) - 4
= 30x^3 - 12x + 44

i got that as well and simplified a bit further
15x^3 - 6x + 22

can it be simplified further?

Kudos [?]: 292 [0], given: 0

Manager
Joined: 02 Aug 2007
Posts: 145

Kudos [?]: 51 [0], given: 0

### Show Tags

20 Oct 2007, 12:00
Do they want the answer as an integer or as an expression?

Here's a simplified expression:
15x^3-6x+22

Kudos [?]: 51 [0], given: 0

Director
Joined: 11 Jun 2007
Posts: 909

Kudos [?]: 292 [0], given: 0

### Show Tags

20 Oct 2007, 12:02
beckee529 wrote:
bkk145 wrote:
inwosu wrote:
f(x)=5x^3-2x+8 and g(x)=6x-4

what is g((f(x))?

g((f(x)) = g(5x^3-2x+8)
= 6*(5x^3-2x+8) - 4
= 30x^3 - 12x + 44

i got that as well and simplified a bit further
15x^3 - 6x + 22

can it be simplified further?

the furthest i can go is

3x(5x^2 - 2) +22

Kudos [?]: 292 [0], given: 0

Intern
Joined: 22 Sep 2007
Posts: 32

Kudos [?]: 2 [0], given: 0

### Show Tags

20 Oct 2007, 12:49
bkk145 is right. The answer is = 30x^3 - 12x + 44 all the answer choices are similar

Kudos [?]: 2 [0], given: 0

VP
Joined: 10 Jun 2007
Posts: 1434

Kudos [?]: 370 [0], given: 0

### Show Tags

20 Oct 2007, 13:16
I don't think you can simplify the equation b/c you don't know what g(x) equals to.

Kudos [?]: 370 [0], given: 0

SVP
Joined: 01 May 2006
Posts: 1794

Kudos [?]: 169 [0], given: 0

### Show Tags

21 Oct 2007, 01:37
bkk145 wrote:
I don't think you can simplify the equation b/c you don't know what g(x) equals to.

Absolutely ... We cannot simplify

g(x) = 30x^3 - 12x + 44... We are not with = 30x^3 - 12x + 44 = 0 for instance.

But we could factorize and that's a way some people simplify in roots

Kudos [?]: 169 [0], given: 0

21 Oct 2007, 01:37
Display posts from previous: Sort by

# f(x)=5x^3-2x+8 and g(x)=6x-4 what is g((f(x))

Moderator: chetan2u

 Powered by phpBB © phpBB Group | Emoji artwork provided by EmojiOne Kindly note that the GMAT® test is a registered trademark of the Graduate Management Admission Council®, and this site has neither been reviewed nor endorsed by GMAC®.